Pediatric inflammatory bowel disease and cancer - Zheng, Jia-Jing; Wu, Zhi-Fei; Hu, Yi-Bing (Frontiers in Immunology, 2025)
BackgroundChildren with inflammatory bowel disease (IBD) have a higher risk of cancer due to prolonged exposure to chronic inflammation and immunosuppressive therapies.MethodsA comprehensive review of extant literature was performed. Findings: The cancer landscape in pediatric IBD is complex, with colorectal cancer, small intestine cancer, lymphoma, cholangiocarcinoma/hepatocellular carcinoma, and skin cancer being predominant concerns. The underlying pathogenic mechanisms involve genomic instability induced by chronic inflammation, carcinogenic effects of immunosuppressants, and environmental factors (e.g., high-fat diet and air pollution). Effective cancer surveillance is crucial in mitigating risk. Strategies include early endoscopic monitoring for high-risk populations, routine dermatological assessments, and clinical monitoring for tumor-related symptoms.ConclusionThis review synthesizes current evidence on the epidemiological characteristics, pathogenic mechanisms, and clinical management strategies for IBD-related malignancies in children. An in-depth characterization of the mechanisms by which pediatric IBD contributes to tumorigenesis is essential for developing surveillance protocols and advancing research to reduce tumor-associated morbidity.